2016
DOI: 10.1371/journal.pone.0164646
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Pharmacologic and Pharmacokinetic Properties of CCX168, a Potent and Selective Orally Administered Complement 5a Receptor Inhibitor, Based on Preclinical Evaluation and Randomized Phase 1 Clinical Study

Abstract: The complement 5a receptor has been an attractive therapeutic target for many autoimmune and inflammatory disorders. However, development of a selective and potent C5aR antagonist has been challenging. Here we describe the characterization of CCX168 (avacopan), an orally administered selective and potent C5aR inhibitor. CCX168 blocked the C5a binding, C5a-mediated migration, calcium mobilization, and CD11b upregulation in U937 cells as well as in freshly isolated human neutrophils. CCX168 retains high potency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 30 publications
5
89
0
5
Order By: Relevance
“…Here we demonstrated that inhibition of C5a receptor attenuates the up-regulation of activated Mac-1 on APS IgG-stimulated neutrophils ( Figure 4D). These data are consistent with previous studies demonstrating that C5a receptor contributes to up-regulation of Mac-1 (32,33).…”
Section: Discussionsupporting
confidence: 94%
“…Here we demonstrated that inhibition of C5a receptor attenuates the up-regulation of activated Mac-1 on APS IgG-stimulated neutrophils ( Figure 4D). These data are consistent with previous studies demonstrating that C5a receptor contributes to up-regulation of Mac-1 (32,33).…”
Section: Discussionsupporting
confidence: 94%
“…However, the selective C5aR1 antagonist PMX53 [43] ablated the C5a-induced CD11b expression on monocytes. This indicates that C5a-mediated induction of CD11b in human monocytes is wholly dependent upon C5aR1 signaling, similar to that described for human neutrophils [44].…”
Section: (A) (B)supporting
confidence: 72%
“…5. This indicates that C5a-mediated induction of CD11b in human monocytes is wholly dependent upon C5aR1 signaling, similar to that described for human neutrophils [44]. The blood samples from healthy donors were preincubated with eritoran, eculizumab (Eculiz.…”
Section: Discussionmentioning
confidence: 63%
“…There is growing evidence to suggest the role of complement activation in glomerular disease in general. Avacopan, previously called CCX168, is an orally administered small-molecule C5aR antagonist that blocks the effects of C5a and prevented the development of GN induced by anti-myeloperoxidase antibodies in a murine model of ANCA associated vasculitis (AAV) [37]. Jayne et al [38] recently studied the drug as a potential steroid-sparing agent in the treatment of this disease.…”
Section: Current Therapy For Anca-positive Rpgnmentioning
confidence: 99%